Otogenic brain abscess and its management with review of literature - Melkundi, Sateesh; Melkundi, Renuka S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Proper management of chronic otitis media may reduce the incidence of otogenic brain abscess. The objective of this study is to present our experience in the management of otogenic brain abscess by neurosurgical and otolaryngological surgery simultaneously. Methods: It is a retrospective study conducted between 2006-2015. 20 patients with otogenic brain abscess were admitted to neurosurgery and ENT wards for management were included in the study. On admissions patients had ENT, neurosurgery and neurological examinations. All the patients underwent neurosurgery followed by mastoidectomy. Repeat CT scanning/ MRI scanning done after 1 week to check for the success of the surgery and discharged on the 10th day after suture removal. Patients were followed up for 1-2 years. Results: The study included sixteen males and four females. Their age ranged between 4-32 years with mean of 18 years. Their chief complaints were severe headache, vomiting and fever with unilateral and or bilateral foul smelling discharge. Brain and HRCT temporal bone CT scanning showed equal incidence of abscess on the sides with 8 cerebellar, 6 temporal, 5 tempero parietal and 1 fronto parietal abscess. After completion of surgery, eighteen patients improved and two patents expired due to septic shock. Conclusions: This is technically more feasible technique with an added advantage of single anaesthesia, short stay of patient in the hospital and early disease clearance in the same procedure.